Analisis Alih Kode dalam Novel Sekosong Jiwa Kadaver Karya Ita Fajria Tamim - ruk'yah, ruk'yah; Anggarista, Randa; Riadi, Selamet (Universitas Qamarul Huda Badaruddin, 2023)
This study aims to describe the forms and functions of code-switching found in Ita Fajria Tamim’s novel Sekosong Jiwa Kadaver. The research employed a qualitative approach with descriptive analysis. The data consisted of dialogue excerpts containing internal and external code-switching. The findings reveal two main forms: internal code-switching (Indonesian–Javanese) and external code-switching (Indonesian–English). The functions of code-switching are influenced by factors such as speaker aspects, interlocutor, presence of a third speaker, humor, and message emphasis. These results highlight that code-switching is not only a linguistic phenomenon but also a cultural and social representation that enriches communication dynamics in literary works.